Volatility Impact of Covid–19 on Macro-Economic Indicators in India - Pal, Soumyadip; Kanoujiya, Jagjeevan; Rastogi, Dr. Shailesh; AGARWAL, BHAKTI (International Journal of Contemporary Economics and Administrative Sciences, 2023)
Covid-19 (C-19) has resulted in economic and financial meltdowns across the world. The counter measures to tackle the virus created economic loss for people from every stratum. Macro-economic indices like unemployment, inflation, and GDP growth rates were severely hit. This study estimates the C-19’s volatility impact on four macroeconomic variables (gold-prices, interest rate, crude oil prices, and exchange rate in the Indian economy. The paper uses daily timeseries data of the macro-economic variables and cases of C-19 in India for the period from 5th January 2020 to 4th April 2022. The volatility impact of Covid19 is measured using Bi-Variate GARCH models. The GARCH models (BEKK-GARCH [BG] and DCC-GARCH [DG]) provide robust results. The result finds existence of both short and long-term C-19’s volatility impact on all variables, although in different degrees. This paper significantly contributes to existing literature and delivers key implications to policymakers to critically treat C-19 for economic stability while making policies. Keywords: Covid-19, macro-economic variables, BEKK-GARCH, DCC-GARCH